Protective Effects of Astragalus Saponin I on Early Stage of Diabetic Nephropathy in Rats - Xiaoxing Yin; Yindi Zhang; Haiwei Wu; Xiang Zhu; Xiaogang Zheng; Shaojun Jiang; Haitong Zhuo; Jianping Shen; Limin Li; Jun Qiu (Elsevier, 2004)
Diabetic nephropathy (DN) has become the leading cause of end stage failure, but no renoprotective treatment has been very available for use in DN. Astragalus saponin I (AS I), a component extracted from Astragalus membranaceus BUNGE, was studied in experimental DN induced by administration of streptozotocin in male rats. The early DN rats were treated with 3 doses of AS I for 8 weeks to analyze its efficacy with different parameters. By comparison with vehicle-treated DN rats, the renal hypertrophy, the oxidative stress intensity, and the blood glucose level of DN rats were ameliorated by AS I. Also, the microalbuminuria level, advanced glycated end-products either in serum or in kidney cortex, and the aldose reductase activity were significantly reduced. Furthermore, the expression of transforming growth factor β1 mRNA in kidney cortex by RT-PCR analysis was markedly declined. Both the relative grade of mesangium hyperplasia by microscopical observation and the thickness of glomerular base membrane by electron microscope measurement were decreased significantly. Therefore, the results suggest that AS I has therapeutic effects on several pharmacological targets in the progress of DN and is a potential drug for prevention of early stage DN. Keywords:: Astragalus membranaceus, Astragalus saponin I, diabetic nephropathy